Analisis Hasil Tes Keterampilan Berpikir Kritis Siswa pada Materi Gerak Parabola - Leni Marlina; Anisa Ramadhani (Program Studi Pendidikan Fisika, UIN Raden Fatah Palembang, 2023)
This study aims to describe students' critical thinking skills on projectile motion at SMA Srijaya Negara. The research method used is the quantitative descriptive method. The test was given to 101 students of classes X IPA. In general, the results of the research show that the critical thinking skills of SMA Srijaya Negara in X grade on projectile motion are still very low. Observing and judging observation is the highest sub-indicator of critical thinking skills in three classes: X IPA 1 (74,29%), X IPA 2 (45,45%), and X IPA 3 (48,48%). Meanwhile, the lowest is focusing on a question at X IPA 1 (2,86%) and X IPA 2 (0,00%). At X IPA 3, the lowest are deducing and judging deductions (0,00%) and making and judging value judgments (0,00%). Because of this, students' critical thinking skills still need to be improved. Students must be more active in their learning, and teachers must encourage students to think critically.